A Systematic Review and Critical Appraisal of Peri-Procedural Tissue Perfusion Techniques and their Clinical Value in Patients with Peripheral Arterial Disease. (December 2021) - Wermelink, Bryan; Ma, Kirsten F.; Haalboom, Marieke; El Moumni, Mostafa; de Vries, Jean-Paul P.M.; Geelkerken, Robert H.
Abstract : Objective: Many techniques have been introduced to enable quantification of tissue perfusion in patients with peripheral arterial disease (PAD). Currently, none of these techniques is widely used to analyse real time tissue perfusion changes during endovascular or surgical revascularisation procedures. The aim of this systematic review was to provide an up to date overview of the peri-procedural applicability of currently available techniques, diagnostic accuracy of assessing tissue perfusion and the relationship with clinical outcomes. Data Sources: MEDLINE, Embase, CINAHL, and the Cochrane Central Register of Controlled Trials. Review Methods: This systematic review was conducted in accordance with the Preferred Reporting Items for Systematic review and Meta-Analysis (PRISMA) guidelines. Four electronic databases were searched up to 31 12 2020 for eligible articles: MEDLINE, Embase, CINAHL and the Cochrane Central Register of Controlled Trials. Eligible articles describing a perfusion measurement technique, used in a peri-procedural setting before and within 24 hours after the revascularisation procedure, with the aim of determining the effect of intervention in patients with PAD, were assessed for inclusion. The QUADAS-2 tool was used to assess the risk of bias and applicability of the studies. Results: An overview of 10 techniques found in 26 eligible articles focused on study protocols, research goals, and clinical outcomes is provided. Non-invasive techniques included laser speckle contrast imaging, micro-lightguide spectrophotometry, magnetic resonance imaging perfusion, near infrared spectroscopy, skin perfusion pressure, and plantar thermography. Invasive techniques included two dimensional perfusion angiography, contrast enhanced ultrasound, computed tomography perfusion imaging, and indocyanine green angiography. The results of the 26 eligible studies, which were mostly of poor quality according to QUADAS-2, were without exception, not sufficient to substantiate implementation in daily clinical practice. Conclusion: This systematic review provides an overview of 10 tissue perfusion assessment techniques for patients with PAD. It seems too early to appoint one of them as a reference standard. The scope of future research in this domain should therefore focus on clinical accuracy, reliability, and validation of the techniques.